Biodegradable biocomposite starch based films blended with chitosan and gelatin - Nurul Nadiah, Md Aini (2010)
The use of petroleum based plastic cause serious damage to environment and the plastic takes a long time to degrade. Thus, the existence of biodegradable plastic may serve as a promising solution to this problem. The objectives of this study are to produce biodegradable biocomposite film from starch, chitosan and gelatin and to study the characterization of biocomposite film in chemical and mechanical properties and biodegradability. This research was conducted by manipulating the concentration of starch from 1 to 5 % while the concentration of chitosan and gelatin was kept constant at 2%. The films were obtained by using mixing and casting method before leave in oven overnight for drying process. The characteristic of biocomposite films were evaluated using equipments like Universal Testing Machine, Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) observation and gas pycnometer. The films also characterized in moisture and water absorption and biodegradability using soil burial degradation test. The film at 3% starch blended with 2% of chitosan and 2% gelatin showed the highest density, the lowest moisture and water absorption and exhibits a smooth surface with less agglomerates and no visible pore. These properties make the film perfect for food packaging application. The FTIR test identified O-H stretching, C-H stretching and C=O stretching were at peak of 3279- 3325, 2930-2932 and 1647 cm-1 respectively. The films also fully degrade within 20 days, and the degradation rate is considered high. However, the film at 1% starch concentration exhibit the stronger tensile stress due to high formation of inter-molecular hydrogen bonds between chitosan and starch. The formation of hydrogen bond is inversely proportional with starch concentration. As a conclusion, the blended film from starch, chitosan and gelatin had potential application in future to be used as food packaging because it can improved foods quality and at the same time conserve the environment.